A simulation-based framework for multi-individual circadian re-entrainment using a single light schedule. (1st February 2023) - Mohamed, Anas; Kalavally, Vineetha; Khong, Yin Jou; Tan, Chee Pin; Cain, Sean W.; Phillips, Andrew J.K.
Abstract: Circadian misalignment is experienced by travelers, shift workers, and people with irregular sleep patterns. Circadian misalignment leads to lower cognitive alertness and increases the risk of poor health outcomes. Since the circadian system is highly responsive to light, circadian rhythms can be realigned using lighting interventions in a built environment. However, inter-individual differences pose an unsolved problem in the implementation of such lighting interventions, particularly for individuals in a shared living space. Here, we present a novel method to converge on schedules of light exposure that can align the circadian rhythms of a group of individuals with different intrinsic circadian periods, within an optimal time. We used an experimentally validated limit-cycle oscillator model of the human circadian system to set a target in the phase and amplitude of the circadian oscillator. An iterative process then changes the switching times of a light/dark bang-bang input to minimize the difference in circadian amplitude and phase to arrive at the target. The proposed method successfully generated schedules of light exposures that optimized the time required for re-entrainment of multiple individuals with circadian phase shifts up to 12 h advance or delay. This method offers a novel solution to improve circadian entrainment under the practical constraint of multiple individuals in a shared living space. Highlights: Optimized lighting to re-entrain the circadian rhythm of a group of individuals. Modified switch time optimization method for fast convergence. Optimized lighting schedules to cater for differences in intrinsic circadian period. Analysed impacts of optimized schedules with different illumination levels.